Learning Transfer in Socioeconomically Differentiated Outdoor Adventure Education Students. (September 2019) - Meerts-Brandsma, Lisa; Sibthorp, Jim; Rochelle, Shannon
Background: The relevance of outdoor adventure education (OAE) programs to diverse participants has been questioned by numerous scholars. Limited research exists about similarities in learning outcomes across categories of difference such as race and socioeconomic status.Purpose : This study focused on understanding how learning outcomes differed between students who did and did not receive scholarships to attend an OAE program and whether students apply what they learn in OAE to their lives similarly.Methodology/Approach : Twenty-one students who enrolled on a National Outdoor Leadership School (NOLS) course between 2010 and 2012 participated in semi-structured interviews 5 years after course completion. Half received scholarships. Participants were matched by course.Findings/Conclusions : Regardless of group, students reported learning comparable lessons and using what they learned in OAE similarly. What differed was the transfer context, meaning the conditions where students applied their learning. Scholarship students do vary demographically from non-scholarship students, but most students in both groups attended college during or after NOLS. This may explain why they applied their learning in similar ways.Implications : OAE practitioners can anticipate that most OAE students will learn the outcomes targeted through the program design and delivery regardless of scholarship status.